Stimuli‐Mediated Specific Isolation of Exosomes from Blood Plasma for High‐Throughput Profiling of Cancer Biomarkers. Issue 2 (19th December 2021) - Liu, Xuehui; Zong, Zhiyou; Liu, Xinzhuo; Li, Qiang; Li, Ang; Xu, Chen; Liu, Dingbin
Abstract: Exosomes, ranging from 30–150 nm in diameter, have emerged as promising non‐invasive biomarkers for the diagnosis and prognosis of numerous diseases. However, current research on exosomes is largely restricted by the lack of an efficient method to isolate exosomes from real samples. Herein, the first stimuli‐mediated enrichment and purification system to selectively and efficiently extract exosomes from clinical plasma for high‐throughput profiling of exosomal mRNAs as cancer biomarkers is presented. This novel isolation system relies on specific installation of the stimuli‐responsive copolymers onto exosomal phospholipid bilayers, by which the enrichment and purification are exclusively achieved for exosomes rather than the non‐vesicle counterparts co‐existing in real samples. The stimuli‐mediated isolation system outperforms conventional methods such as ultracentrifugation and polyethylene glycol‐based precipitation in terms of isolation yield, purity, and retained bioactivity. The high performance of the isolation system is demonstrated by enriching exosomes from 77 blood plasma samples and validated the clinical potentials in profiling exosomal mRNAs for cancer diagnosis and discrimination with high accuracy. This simple isolation system can boost the development of extracellular vesicle research, not limited to exosomes, in both basic and clinical settings. Abstract : A stimuli‐mediated isolation system is rationally designed and developed for the specific extraction of exosomes from clinical plasma with high yield, high purity, and retained bioactivity. The isolated exosomes are analyzed for high‐throughput profiling of cancer‐related mRNAs, allowing cancer diagnosis and discrimination with high accuracy.